Integrative Omics -approach discovers dynamic and regulatory features of bacterial stress responses - Berghoff, Bork A.; Konzer, Anne; Mank, Nils N.; Looso, Mario; Rische, Tom; Förstner, Konrad U.; Krüger, Marcus; Klug, Gabriele; Justus Liebig University Giessen (My University, 2013)
Bacteria are frequently exposed to disadvantageous conditions, like elevated temperatures or nutrient depletion. The ability to maintain viable populations is based on cellular stress responses, which are regulated in a complex manner with different outputs on different regulatory levels. For example, mRNA levels do not ultimately determine protein amounts since translation of mRNAs can be influenced irrespective of mRNA levels. To appreciate nature and frequency of these regulatory events, multi-layered experimental approaches are required on a global scale. The photo-oxidative stress response of the purple bacterium Rhodobacter sphaeroides was chosen as a model. Changes of total mRNAs (transcriptome) and ribosomal-bound mRNAs (translatome) were monitored by microarrays. The proteome was assessed by mass spectrometry, applying a bacterial SILAC standard for indirect quantification, an approach which additionally identified new open reading frames. Integration of the three expression levels provided a comprehensive insight into regulatory events and identified new stress-responsive genes, including genes for transcriptional regulators and for quorum sensing. We found that translational control exceeds simple regulation on the transcriptional level. Furthermore, polar expression patterns within inducible operons point at the possibility of expression fine-tuning by gene positioning.
Keywords: ddc:570